Oocyte and Embryo Manipulation and Epigenetics - Osman, Emily; Franasiak, Jason; Scott, Richard (Seminars in Reproductive Medicine, 2018)
Regulation of the epigenome is a mechanism by which the environment influences gene expression and consequently the health of the individual. The advent and refinement of novel assisted reproductive technology (ART) laboratory techniques, including vitrification, dynamic culture systems, oocyte in vitro maturation, laser-assisted hatching, intracytoplasmic sperm injection, and preimplantation genetic testing for aneuploidy have contributed to the success of ART. From fertilization through implantation, the epigenetic profile of the embryo changes dynamically. Concurrently with these changes, embryo development in vitro is dependent on laboratory intervention and manipulation to optimize outcomes. The impact of ART techniques on imprinting errors remains unclear, as the infertile population likely confers an independent risk factor for defects in expected epigenetic patterns. Alternations in epigenetic mechanisms may contribute to the incidence of aneuploidy as well as recurrent implantation failure of euploid embryos. Additional investigative efforts are needed to assess the contribution of oocyte and embryo manipulation on imprinting modifications in this vulnerable population. The development of diagnostic modalities involving the discovery of epigenetic alterations to improve in vitro fertilization outcomes is an exciting and promising area of future study.
Keywords: oocyte; embryo manipulation; epigenetics